Use of Electrocardiography to Predict Future Development of Hypertension in the General Population. Issue 17 (April 2016) - Takase, Hiroyuki; Sugiura, Tomonori; Murai, Shunsuke; Yamashita, Sumiyo; Ohte, Nobuyuki; Dohi, Yasuaki
Abstract : Abstract: Cardiac muscle responds to increased afterload by developing hypertrophy. During the early stages of hypertension, the heart can be transiently, but frequently, exposed to increased afterload. This study was designed to test the hypothesis that left ventricular hypertrophy (LVH) assessed by electrocardiography (ECG) can be used to predict future development of hypertension. Sokolow–Lyon voltage and Cornell product were calculated using ECG in 5770 normotensive participants who visited our hospital for a physical checkup (age 52.7 ± 11.3 years). LVH was defined as a Sokolow–Lyon voltage of >3.8 mV or a Cornell product of >2440 mm × ms. After baseline examination, participants were followed up with the endpoint being the development of hypertension. During the median follow-up period of 1089 days (15, 789 person-years), hypertension developed in 1029 participants (65.2/1000 person-years). A Kaplan–Meier analysis demonstrated a significantly higher incidence of hypertension in participants with LVH than in those without LVH as assessed by Sokolow–Lyon voltage or Cornell product ( P  < 0.0001 for both). The hazard ratios for incident hypertension in participants with LVH defined by Sokolow–Lyon voltage and Cornell product were 1.49 (95% confidence interval [CI] 1.16–1.90, P  < 0.01) and 1.34 (95% CI 1.09–1.65, P  < 0.01), respectively, after adjustment for possible risk factors. Furthermore, in multivariable Cox hazard analysis, where Sokolow–Lyon voltage and Cornell product were taken as continuous variables, both indices were independent predictors of future hypertension ( P  < 0.0001). Both Sokolow–Lyon voltage and Cornell product are novel predictors of future development of hypertension in the general population.